2023
DOI: 10.5694/mja2.51948
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing of psychotropic medications to Australian children and adolescents before and during the COVID‐19 pandemic, 2013–2021: a retrospective cohort study

Abstract: Objective To determine longitudinal patterns of dispensing of antidepressant, anxiolytic, antipsychotic, psychostimulant, and hypnotic/sedative medications to children and adolescents in Australia during 2013–2021. Design Retrospective cohort study; analysis of 10% random sample of Pharmaceutical Benefits Scheme (PBS) dispensing data. Participants, setting People aged 18 years or younger dispensed PBS‐subsidised psychotropic medications in Australia, 2013–2021. Main outcome measures Population prevalence of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The most substantial increases in rates and trends of prescriptions concerned anxiolytic, hypnotic and sedative, and antidepressant medications. This finding is in line with the growing prevalence of mood and anxiety disorders recently reported in the pediatric population, whose first-line treatment often involves the prescribing of these specific psychotropic medication classes . Before the pandemic onset, anxiolytics and hypnotics and sedatives were the only psychotropic medication classes with decreasing prescription trends in the pediatric population in France.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The most substantial increases in rates and trends of prescriptions concerned anxiolytic, hypnotic and sedative, and antidepressant medications. This finding is in line with the growing prevalence of mood and anxiety disorders recently reported in the pediatric population, whose first-line treatment often involves the prescribing of these specific psychotropic medication classes . Before the pandemic onset, anxiolytics and hypnotics and sedatives were the only psychotropic medication classes with decreasing prescription trends in the pediatric population in France.…”
Section: Discussionsupporting
confidence: 71%
“…Antipsychotic medications are usually prescribed for the treatment of psychotic and conduct disorders and only as second-line treatments for major behavioral and bipolar disorders . Finally, despite a more steeply increasing trend after the pandemic onset, prescriptions of psychostimulants did not rise above expected rates in France, as opposed to other countries . This finding should be interpreted with caution, as the acceleration of the prescription trend may also be associated with a modification of methylphenidate prescribing conditions in France.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increase observed in 2020 in Italy, the comparison with published international epidemiological studies performed at the onset of the COVID-19 pandemic showed that the prescription of psychotropic medications in Italian paediatric population resulted still much lower than those observed in the USA, Australia and in some EU countries [ 42 , 45 , 46 , 49 , 51 ].…”
Section: Discussionmentioning
confidence: 93%
“…When comparing April 2020 − 2019, antipsychotics had the largest year-over-year percent change (41.9%), followed by antidepressants (37.9%), mood stabilizers (34.4%), and ADHD medications (20.4%); in September 2020, when the number of treated youths was similar to pre-pandemic, the year-over-year percent change in ADHD medication prescription decreased (− 2.8%), while other psychotropic classes increased between 3.1% and 5.0% compared to September 2019 [ 45 , 46 ]. A marked increase in psychotropic medications use in children and adolescents was also observed in Australia [ 47 , 48 ], with a prevalence passing from 33.8 to 60.0 per 1,000 children between 2013 and 2021 [ 49 ].…”
Section: Discussionmentioning
confidence: 99%